Imobilização de ferro (II) em matriz de alginato e sua utilização na degradação de corantes têxteis por processos Fenton - Souza,Kely Viviane de (Sociedade Brasileira de Química, 2008)
In this work Fenton and photo-Fenton processes for textile dye degradation were investigated using iron (II) immobilized in alginate spheres. Photomicrographs obtained by scanning electron microscopy showed an irregular and porous surface with a homogeneous distribution of iron. The Fenton process was used to evaluate the degradation efficiency of reactive dyes and this procedure showed a low degradation effect. The association of artificial visible light or solar radiation in the Fenton process (foto-Fenton process) showed degradation ratios of 70 and 80% respectively in 45 min. It was also observed that the iron-alginate matrix can be reused.